Multicystic ameloblastoma of fast growing with partial reconstruction - Samuel Urbano del Valle; Eilien Tovío Martínez; Erich López Aparicio (Editorial Ciencias Médicas, 2018)
Introduction: Ameloblastoma is a benign neoplasm that tends to be locally aggressive, with a high tendency to relapse. It is an odontogenic tumor of epithelial origin; 80% of cases occur at the mandibular level, both in branch and at an angle. It usually manifests during the third to fifth decade of life. The clinical characteristics are not determinants for the biological behavior or the prognosis of an ameloblastoma, even in many of the cases in which they are complemented with radiographs and/or histopathological samples. Objective: To report the surgical management of multicystic ameloblastoma in a radical way through a wide resection and placement of a reconstruction plate that functioned as a space maintainer, due to its unusual rapid growth. Case presentation: A clinical case of a male patient is described, who presents a tumor lesion in the right mandibular branch, with a clinical appearance of a multicystic, fast growing, follicular ameloblastoma, treated at Hospital Universitario del Caribe in Cartagena, Colombia. Data were provided on its clinical appearance, its rapid evolution, the histopathological findings and the therapeutic management performed. Conclusions: Due to its rapid growth, for this particular case, the most feasible option was to carry out the total resection of the lesion in order to avoid or reduce the possibility of relapse, followed by reconstruction with an osteosynthesis plate to restore the functionality of the temporomandibular joint and of the mandibular bone, without leaving aside the aesthetics of the patient.